2017
DOI: 10.1016/j.ebiom.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Violet Light Exposure Can Be a Preventive Strategy Against Myopia Progression

Abstract: Prevalence of myopia is increasing worldwide. Outdoor activity is one of the most important environmental factors for myopia control. Here we show that violet light (VL, 360–400 nm wavelength) suppresses myopia progression. First, we confirmed that VL suppressed the axial length (AL) elongation in the chick myopia model. Expression microarray analyses revealed that myopia suppressive gene EGR1 was upregulated by VL exposure. VL exposure induced significantly higher upregulation of EGR1 in chick chorioretinal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
156
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(169 citation statements)
references
References 48 publications
7
156
0
6
Order By: Relevance
“…In fish, chicks, and guinea pigs, eyes were less myopic when raised under short wavelength (violet and blue) light compared to those raised under longer wavelength (green or red) light. 209,212,[218][219][220][221] In these studies, short-term eye growth matched the direction and magnitude predicted by LCA. 212,222 However, longerterm eye growth under these same conditions surpassed what would be predicted by LCA, indicating a more complex interaction between chromatic cues and other signals for eye growth.…”
Section: Spectral and Temporal Characteristics Of Lightsupporting
confidence: 71%
See 1 more Smart Citation
“…In fish, chicks, and guinea pigs, eyes were less myopic when raised under short wavelength (violet and blue) light compared to those raised under longer wavelength (green or red) light. 209,212,[218][219][220][221] In these studies, short-term eye growth matched the direction and magnitude predicted by LCA. 212,222 However, longerterm eye growth under these same conditions surpassed what would be predicted by LCA, indicating a more complex interaction between chromatic cues and other signals for eye growth.…”
Section: Spectral and Temporal Characteristics Of Lightsupporting
confidence: 71%
“…Animal studies have shown conflicting results across species with respect to the influence of spectral composition of light on eye growth. In fish, chicks, and guinea pigs, eyes were less myopic when raised under short wavelength (violet and blue) light compared to those raised under longer wavelength (green or red) light . In these studies, short‐term eye growth matched the direction and magnitude predicted by LCA .…”
Section: Spectral and Temporal Characteristics Of Lightmentioning
confidence: 50%
“…Animal studies have demonstrated that blue light has a suppressive effect against myopia [68,69]. Recently, Torri et al [70] proposed that violet light (VL) (which has a shorter wavelength than blue light), which is a missing light component in indoor environments, may play a role in the inhibition of myopia development and progression. They demonstrated that exposure to VL inhibited myopic shift and axial elongation in chicks.…”
Section: Others: Outdoor Activities and Violet Light Transmitting Lensesmentioning
confidence: 99%
“…Further research is required to analyse this issue in more depth. In the meantime, manufacturers of luminous devices for newborn infants could avoid deep blue, prefer the use of warm white light and limit the radiance in white light to few hundreds of W/(m 2 .sr); parents should also be educated to take care with luminous environment of their young children, keeping in mind, however, that shortwavelengths light is necessary to child eyes growth and must naturally not be deleted from their visual environment (Downie, 2017;Torii et al, 2017).…”
Section: Resultsmentioning
confidence: 99%